Food fraud and the partnership for a ‘healthier’ America: a case study in state-corporate crime - León, Kenneth Sebastian (Critical criminology, 2017)
At a moment of heightened public concern over food-related health issues, major corporations in the food industry have found their products and practices under scrutiny. Needing to be understood as socially responsible, these corporations have established partnerships with the state to construct a positive, proactive, and cooperative public image. One major public-private partnership that evolved from former First Lady Michelle Obama’s Let’s Move initiative - the Partnership for a Healthier America - serves as a case study in this paper, which analyzes the consequences and social harms perpetuated by a public health campaign bound by the imperative to maximize profit. By using trusted state actors to deliver accurate but deceptive claims about food companies’ commitment to public health, this public-private partnership actively misleads the public and potentially exacerbates public health challenges, warranting a skeptical revision of how we understand corporate social responsibility and neoliberal governance on issues of health and nutrition. As a form of fraud, these attempts to mislead the public go beyond the actions of public sector individuals or members of corporate boards, but are structurally incentivized by the legal rights, regulatory privileges, and profit-related incentives central to the modern corporate form. While conventional criminological research tends to underemphasize state and corporate harms, we make use of a critical criminological perspective to analyze state-corporate partnerships in the space between food industry practices and public health policy.